Spatial-temporal comparison of Eph/Ephrin gene expression in ocular lenses from aging and knockout mice - Huynh, Peter N.; Cheng, Catherine (Frontiers in Ophthalmology, 2024)
Cataracts, defined as any opacity in the transparent ocular lens, remain the leading cause of blindness and visual impairment in the world; however, the etiology of this pathology is not fully understood. Studies in mice and humans have found that the EphA2 receptor and the ephrin-A5 ligand play important roles in maintaining lens homeostasis and transparency. However, due to the diversity of the family of Eph receptors and ephrin ligands and their promiscuous binding, identifying functional interacting partners remains a challenge. Previously, 12 of the 14 Ephs and 8 of 8 ephrins in mice were characterized to be expressed in the mouse lens. To further narrow down possible genes of interest in life-long lens homeostasis, we collected and separated the lens epithelium from the fiber cell mass and isolated RNA from each compartment in samples from young adult and middle-aged mice that were either wild-type, EphA2–/– (knockout), or ephrin-A5–/–. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was implemented to compare transcript levels of 33 Eph and ephrin gene variants in each tissue compartment. Our results show that, of the Eph and ephrin variants screened, 5 of 33 showed age-related changes, and 2 of 33 showed genotype-related changes in lens epithelium. In the isolated fibers, more dynamic gene expression changes were observed, in which 12 of 33 variants showed age-related changes, and 6 of 33 showed genotype-related changes. These data allow for a more informed decision in determining mechanistic leads in Eph-ephrin-mediated signaling in the lens.